2017
DOI: 10.1186/s12864-017-4160-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association mapping of resistance to a Brazilian isolate of Sclerotinia sclerotiorum in soybean genotypes mostly from Brazil

Abstract: BackgroundSclerotinia Stem Rot (SSR), caused by the fungal pathogen Sclerotinia sclerotiorum, is ubiquitous in cooler climates where soybean crops are grown. Breeding for resistance to SSR remains challenging in crops like soybean, where no single gene provides strong resistance, but instead, multiple genes work together to provide partial resistance. In this study, a genome-wide association study (GWAS) was performed to dissect the complex genetic architecture of soybean quantitative resistance to SSR and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 60 publications
2
33
0
1
Order By: Relevance
“…Moreover, most studies focusing on B. napus resistance to S. sclerotiorum also identified GST regardless of the methodologies, GWAS or RNA‐Seq (Girard et al., ; Wei et al., ; Wu, Zhao, Liu, et al., ). A recent GWAS for soybean resistance to S. sclerotiorum also identified soybean GST (Wei et al., ) which was also noted to have high expression in a transcriptomic study (Calla et al., ). Consistently, our results also pointed out GST of pea may play a fundamental role in lesion and nodal resistance to S. sclerotiorum .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, most studies focusing on B. napus resistance to S. sclerotiorum also identified GST regardless of the methodologies, GWAS or RNA‐Seq (Girard et al., ; Wei et al., ; Wu, Zhao, Liu, et al., ). A recent GWAS for soybean resistance to S. sclerotiorum also identified soybean GST (Wei et al., ) which was also noted to have high expression in a transcriptomic study (Calla et al., ). Consistently, our results also pointed out GST of pea may play a fundamental role in lesion and nodal resistance to S. sclerotiorum .…”
Section: Discussionmentioning
confidence: 93%
“…While most of these studies focused on the expression comparisons between a resistant and a susceptible variety, the genetic diversity of white mold resistance in B. napus might be underestimated using only this approach. Genome‐wide association study (GWAS) is a robust approach to map white mold resistance and to capture the resistance diversity in a germplasm collection (Moellers et al., ; Wei et al., , ). The GWAS approach has been demonstrated in soybean ( Glycine max Merr.…”
Section: Introductionmentioning
confidence: 99%
“…In soybean, bi-parental linkage mapping led to the discovery of many quantitative trait loci (QTL) for resistance to this pathogen. Remarkably, a total of 103 QTL on 18 of the 20 soybean chromosomes have been recorded in SoyBase (Grant et al, 2009) with minimal overlap between QTL reported by different studies (Arahana et al, 2001;Huynh et al, 2010;Kim and Diers, 2000;McCaghey et al, 2017;Moellers et al, 2017;Wei et al, 2017). Despite these efforts, gene level and mechanistic details of soybean resistance mechanisms against S. sclerotiorum remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In soybean, Bi-parental linkage mapping led to the discovery of many quantitative trait loci (QTL) for resistance to this pathogen. Remarkably, a total of 103 QTL on 18 of the 20 soybean chromosomes have been recorded in SoyBase (21) with minimal overlap between QTL reported by different studies (9,2226). Despite these efforts, gene level and mechanistic details of soybean resistance mechanisms against S .…”
Section: Introductionmentioning
confidence: 99%